2016
DOI: 10.3390/ijms17081340
|View full text |Cite
|
Sign up to set email alerts
|

Dextran: Influence of Molecular Weight in Antioxidant Properties and Immunomodulatory Potential

Abstract: Dextrans (α-d-glucans) extracted from Leuconostoc mesenteroides, with molecular weights (MW) of 10 (D10), 40 (D40) and 147 (D147) kDa, were evaluated as antioxidant, anticoagulant and immunomodulatory drugs for the first time. None presented anticoagulant activity. As for the antioxidant and immunomodulatory tests, a specific test showed an increase in the dextran activity that was proportional to the increase in molecular weight. In a different assay, however, activity decreased or showed no correlation to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 54 publications
(79 reference statements)
1
14
0
Order By: Relevance
“…Both dextran and Dex–Gal failed to exhibit ferric chelating activity under all tested conditions (from 0.1 to 2 mg/mL). This data corroborates previous data that show dextrans are not good iron chelators [10]. Although GA has iron chelation activity [38], the conjugation of dextran to GA acid did not affect the chelating activity of this polysaccharide.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Both dextran and Dex–Gal failed to exhibit ferric chelating activity under all tested conditions (from 0.1 to 2 mg/mL). This data corroborates previous data that show dextrans are not good iron chelators [10]. Although GA has iron chelation activity [38], the conjugation of dextran to GA acid did not affect the chelating activity of this polysaccharide.…”
Section: Resultssupporting
confidence: 92%
“…Dextran failed to exhibit any positive activity under the conditions evaluated. A previous study also evaluated the scavenging capacity of L. mesenteroides dextran superoxide ions with molecular masses of 10, 40, and 147 kDa and found that only 10 kDa dextran showed high activity (~50%); the activity did not exceed 9% for the other two types [10]. Dextrans from Leuconostoc pseudomesenteroides also showed low activity (about 15%) [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, negatively charged acidic polysaccharides containing higher uronic acid showed higher metal chelating activity [59,60]. Soeiro et al [61] showed some dextrans with 5% of iron chelating activity at a concentration of 2 mg/ml. Only about 10% of iron chelating activity was found for α-glucans isolated from Aconitumm Kusnezoffii [62].…”
Section: Antioxidant Propertiesmentioning
confidence: 98%
“…EPS produced by Bacillus tequilensis FR9 showed potential strong antioxidant effects through scavenging reactive oxygen species (ROS) (Rani et al 2017). The commercial glucan with different molecular weight (1, 4, and 14.7 9 10 4 Da) synthesized by L. mesenteroides exhibited strong antioxidant, anticoagulant and immunomodulatory activities (Soeiro et al 2016). The in vitro antioxidant properties of the EPS showed remarkable scavenging effects on superoxide anion radical and hydroxyl radical (Adesulu-Dahunsi et al 2018).…”
Section: Introductionmentioning
confidence: 99%